Calculation of comfortable thermal conditions for Mersin urban city planning in Turkey - Gungor, Senay; Cetin, Mehmet; Adiguzel, Fatih (Springer Science and Business Media LLC, 2020)
Computer models that evaluate the formulas of these indices together with environmental factors and human characteristics have been created. Physiological equivalent temperature index and classification summer calculation model used for bioclimatic comfort calculations by obtaining monthly data of General Directorate of State Metrology Stations between 1972 and 2018 in Mersin city center. The results, comfortable monthly intervals, were determined and necessary suggestions were made for the people of Mersin city center in a month. In the calculations, the meteorological parameters such as surface-and-air temperature, wind speed, and relative humidity were taken into consideration. Monthly results show the bioclimatically comfortable area in September and May. There are conditions in Mersin that lead to comfortable perceptions in summer. During the cold period, different levels appear and warm and comfortable thermal conditions are observed. GIS analysis was used to determine the development of thermal perceptions over time. It was calculated between 1972 and 2018. According to these coefficients, there is a tendency to increase in PET values in the regions close to the water in Mersin and to decrease in Mersin, which is the station in rural areas, as a city station.
Keywords: Bioclimatic comfort; Mersin; Urban city; 11. Sustainability